2023
DOI: 10.3899/jrheum.220818
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Antineutrophil Cytoplasmic Antibody Renal Risk Score and Modification of the Score in a Chinese Cohort With a Majority of Myeloperoxidase-Positive Patients

Abstract: ObjectiveWe aimed to validate and modify the renal risk score for antineutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis (AAGN) in a Chinese cohort with a majority of myeloperoxidase (MPO)-positive patients.MethodsA total of 285 AAGN patients with biopsy-proven in our center were retrospectively included. Patients were randomly assigned to the development set (n=201) and the validation set (n=84). We calculated the renal risk score and analyzed the clinicopathological characteristics and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…14 The measure used for these models is an extension, Harrell C, which is used for time-to-event studies. Ni et al 3 found that, in their cohort, the ARRS retained strong discriminative ability at C = 0.783, and the nomogram's performance was C = 0.822. The nomogram uses 5 more parameters, and as the number of parameters increases, so does the risk of overfitting.…”
Section: See Aav Nomogram Model Page XXXmentioning
confidence: 94%
See 4 more Smart Citations
“…14 The measure used for these models is an extension, Harrell C, which is used for time-to-event studies. Ni et al 3 found that, in their cohort, the ARRS retained strong discriminative ability at C = 0.783, and the nomogram's performance was C = 0.822. The nomogram uses 5 more parameters, and as the number of parameters increases, so does the risk of overfitting.…”
Section: See Aav Nomogram Model Page XXXmentioning
confidence: 94%
“…In this issue of The Journal of Rheumatology, Ni et al 3 present a new nomogram model for clinical prediction in ANCA-GN. Three prediction models have already been proposed: the Berden classification 4 based on glomerular pathology, the Mayo Clinic Chronicity Score (MCCS) 5 based on 4 components of chronic scarring, and the ANCA Renal Risk Score (ARRS), 6 which uses a combination of histopathologic parameters and biochemical indicators.…”
Section: Editorialmentioning
confidence: 99%
See 3 more Smart Citations